Comprehensive Prosthetic Strategy Through a Staged Approach to Postoperative Obturator Fabrication until Definitive Obturator for Hemimaxillectomy Patient: Case Report - Aris Aji Kurniawan; Franciscus Wihan Pradana; Endang Wahyuningtyas; Sri Budi Barunawati (Jurnal Kesehatan Gigi, 2026)
Hemimaxillectomy is a surgical procedure that involves the removal of part of the palatal and maxillary bones, which results in disruption of the oral cavity structure. This defect causes an abnormal relationship between the oral and nasal cavities, accompanied by abnormalities in the palate and tooth loss. This case report aims to examine the rehabilitation using an obturator of a patient after a hemimaxillectomy procedure. A 32-year-old male patient came to the Dental and Oral Polyclinic of Dr. Sardjito General Hospital, a referral from the Ear, Nose, and Throat Polyclinic with a diagnosis of nasopharyngeal angiofibroma. The treatment management was that the patient underwent a post-surgical obturator before undergoing a hemimaxillectomy. The next stage was the hemimaxillectomy procedure followed by post-surgical obturator insertion. Prosthetic treatment was carried out in stages, including interim and definitive obturator insertion. Objective examination of retention, stabilization, occlusion, phonation, and aesthetics showed they were in good condition after obturator insertion. Obturator prothesis in this case restored patient’s chewing, swallowing, speech, and aesthetic after hemimaxillecromy.